Removal of 2,4-dichlorophenol using cyclodextrin-ionic liquid polymer as a macroporous material: characterization, adsorption isotherm, kinetic study, thermodynamics - Raoov, M.; Mohamad, S.; Abas, M.R. (2013)
Cyclodextrin-ionic liquid polymer (βCD-BIMOTs-TDI) was firstly synthesized using functionalized β-Cyclodextrin (CD) with 1-benzylimidazole (BIM) to form monofunctionalized CD (βCD-BIMOTs) and was further polymerized using toluene diisocyanate (TDI) linker to form insoluble βCD-BIMOTs-TDI. SEM characterization result shows that βCD-BIMOTs-TDI exhibits macropore size while the BET result shows low surface area (1.254m2g-1). The unique properties of the ILs allow us to produce materials with different morphologies. The adsorption isotherm and kinetics of 2,4-dichlorophenol (2,4-DCP) onto βCD-BIMOTs-TDI is studied. Freundlich isotherm and pseudo-second order kinetics are found to be the best to represent the data for 2,4-DCP adsorption on the βCD-BIMOTs-TDI. The presence of macropores decreases the mass transfer resistance and increases the adsorption process by reducing the diffusion distance. The change in entropy (ΔS°) and heat of adsorption (ΔH°) for 2,4-DCP on βCD-BIMOTs-TDI were estimated as -55.99J/Kmol and -18.10J/mol, respectively. The negative value of Gibbs free energy (ΔG°) indicates that the adsorption process is thermodynamically feasible, spontaneous and chemically controlled. Finally, the interactions between the cavity of βCD-BIMOTs and 2,4-DCP are investigated and the results shows that the inclusion of the complex formation and π-π interaction are the main processes involved in the adsorption process.